ANALYZING TEACHING AND LEARNING INTERACTIONS IN ONLINE AND OFFLINE MODES AT TOMAKAKA UNIVERSITY - Gusnawati Honjong; Nurul Hasanah; Muhammad Ybnu Taufan; Syahban Mada Ali (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2025)
This study investigates the differences in teaching and learning interactions among university students in online and offline learning environments, focusing on students from the Faculty of Teacher Training and Education at Universitas Tomakaka, Indonesia. The study was motivated by the emerging need to evaluate how communication patterns and engagement are affected by instructional modalities in the post-pandemic context. Using a mixed-method approach, including questionnaires and semi-structured interviews with 50 randomly selected students, this research explores interactional dynamics and identifies existing gaps in current literature regarding rural-based blended learning practices. The results indicate that offline learning fosters stronger student–lecturer and peer–peer interaction due to richer nonverbal cues and immediacy of feedback, while online learning shows limited engagement, especially in rural settings. However, some students reported higher comfort and participation in digital settings due to reduced social pressure. The study concludes that a blended learning approach, supported by interactive tools and digital training, may optimize communication and inclusiveness. These findings have practical implications for improving instructional design, especially in under-resourced educational institutions, and highlight the importance of digital infrastructure and pedagogical capacity building in enhancing learning interaction.